BOARD CHARACTERISTICS AND AUDIT QUALITY OF LISTED FIRMS IN NIGERIA: THE MODERATING ROLE OF AUDIT COMMITTEE GENDER - Ebele, Edochie Elsie; Yahaya, Onipe Adabenege; Gambo, Samuel Joshua; Okpanachi, Joshua (Kashere Journal of Management Sciences, 2025)
This study is on board characteristics and Audit quality of listed firms in nigeria: the moderating role of audit committee gender. It is neccessitated by the need to curb financial losses and corporate failures through reliable, true and fair value financial information disclosures for stakeholders in the corporate world. A study sample of 74 firms selected from 148 listed Nigeria firms for the period January 2012 to December 2021 was used for the study and the independent variables; Board size, independence and board gender diversity are the proxies for board characteristics while the dependent variable; audit quality is proxied by the big 4 audit firms. Data sourced from the published accounts of these firms displayed on their websites and from the Nigerian Exchange Group was analysed using multiregression analysis aided by STATA statistical software to accommodate the multivariate variables. Findings of the study provide evidence that board characteristics affect audit quality particularly the inclusion of women on the board through gender diversity. The study then recommended that firms should consider the inclusion of women in their boards.